Coculture of Spheroids/2D Cell Layers Using a Miniaturized Patterned Platform as a Versatile Method to Produce Scaffold‐Free Tissue Engineering Building Blocks. Issue 1 (23rd October 2017) - Oliveira, Nuno M.; Martins‐Cruz, Cláudia; Oliveira, Mariana B.; Reis, Rui L.; Mano, João F.
Abstract: A hanging drop system that allows the multiconfigurational coculture of 3D microtissues is suggested as a versatile platform to promote the formation of functional preconditioned spheroids/microtissues, namely stem‐cell‐derived tissue engineering microtissues, with potential to be applied as scaffold‐free building blocks. Here, superhydrophobic (SH) platforms patterned with wettable regions are adapted for the production and culture of human adipose‐derived stem‐cell spheroids under indirect coculture with 2D layers of different cell types and direct coculture setups. The versatile indirect and direct coculture setups allow the use of cell lines as soluble biomolecules "factories" to continuously modulate microtissues response aspects, including their viability, cell number, and protein expression. This novel application of patterned SH platforms may find application in the massive production of modulated spheroids for the biomedical and pharmaceutical fields, with specific added value in the biofabrication of 3D constructs for tissue regeneration, as disease models, or even for organoids preparation. Abstract : Bioinspired superhydrophobic platforms are suggested for the simple and rapid versatile coculture of 3D spheroids. A hanging drop system is applied for the production of human adipose‐derived stem‐cell spheroids under conditioned direct and indirect coculture setups, which showed the potential to tailor the cell structures' morphology, viability, and protein production.